Fabrication of magnetic silica supported Lewis acidic Al-nanocatalyst for the efficient chemical fixation of CO2 into cyclic carbonates at ambient conditions - Kamrul Hasan; Ihsan A. Shehadi; Mohamed El-Naggar; Monther A․ Khanfar; Shashikant P. Patole; Raed A. Al-Qawasmeh (Chemical Engineering Journal Advances, 2025)
The increasing urgency of carbon capture and utilization demands the development of cost-effective, sustainable catalytic systems for CO2 fixation. In this work, we report the rational design and fabrication of a magnetically separable Lewis acidic nanocatalyst, Fe3O4@SiO2@Propyl@Ldi-Cl-APG@AlCl, engineered to catalyze the cycloaddition of CO2 with epoxides under mild, solvent-free conditions. The catalyst integrates an amino bis(phenolate) ligand functionalized with a COOH pendant arm onto a silica-coated magnetic Fe3O4 core, followed by coordination with AlCl3 to introduce highly active Lewis acid sites. Comprehensive structural and surface characterizations including Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), field-emission scanning electron microscopy (FE-SEM), energy dispersive X-ray spectrometry (EDX), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), computational assessment, and inductively coupled plasma-optical emission spectroscopy (ICP-OES), confirm successful stepwise functionalization, thermal stability, and the uniform dispersion of the aluminum complex. Computational analysis further supports the distorted trigonal bipyramidal geometry around the Al center, elucidating the catalyst’s reactivity. Catalytic performance studies reveal near-quantitative conversion (up to 99 %) of diverse epoxides to cyclic carbonates at ambient temperature and 1.0 bar CO₂, achieving a high turnover number (TON) of 1100 with 0.09 mol % Al loading. The catalyst exhibits remarkable recyclability over five cycles with negligible loss in activity or metal leaching. This work not only advances a structurally well-defined and operationally simple catalytic platform but also addresses key challenges in CO₂ utilization through a green, scalable approach.